Identification of Agronomic Traits of Centella asiatica (L.) Urban. Naturally Grown at Regions With Different Altitudes - Halimi, Entis Sutisna (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
The Centella asiatica is an important herbal plant in Indonesia. The research was done to describe severalagronomic traits that related to yield of the plants grown at regions with different altitudes. The research wascarried out at three different regions of highland, midland, and lowerland, each at >500m, 250-500m, and < 250mabove sea level. The research location was Pagar Alam, Musi Rawas, and Ogan Ilir, respectively. Research indicatedthat the agronomic traits of the plants grown at highland, midland, and lowerland, regions were about the same forgeneral appearance of leaf shape and flower color. The leaf size, number and length of stolone, number of rossets,length of rhizomes, and number of flower were varied depending on the region. The plants grown at highland andmidland region tend to have larger leaf size, shorter petiole and stolone, more number of rossets and stolone,longer rhizomes, and more number of flowers per plant, compared to the plants of lowerland region. This could beindication that Centella asiatica plants grown on midland, and highland were more productive than plants oflowerland region.